Islamic work ethics, performance management and gender difference among Muslim employees / Sarina Muhamad Noor, Shahrul Amri Ab Wahab and Noraini Nasirun@Hirun - Muhamad Noor, Sarina; Ab Wahab, Shahrul Amri; Nasirun@Hirun, Noraini (Universiti Teknologi MARA, Perlis, 2017)
Islamic human resource management observed the concept of tawheed and use Quran and sunnah in accomplishing the human resource function. Thus, the integrity and ethics are very important in ensuring the functions are managed effectively. Previous studies on Islamic human resource have discussed on the functions and organization performance. As few have investigated on Islamic ethics, this study focused in determining the relationship between Islamic work ethic, performance and gender differences in performance management. The study was conducted in Malaysia among employees of Islamic organizations using self- administered questionnaires. Findings reveal that there is a significant relationship between ethics and performance management. In addition, the mean differences between genders is also significant. Several implications were discussed at the end of the paper.